Faktor Eksternal dan Internal Masyarakat Blora Terhadap Kepatuhan Wajib Pajak Bumi dan Bangunan - Eka Candra Ameria Wahyuningtiyas; Aji, Nur Prasetyo (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze external and internal factors influencing land and building tax compliance in Banjarejo District, Blora. The research employs a quantitative approach using accidental sampling, with samples drawn from taxpayers based on the 2024 SPPT data. Data collection was conducted through questionnaires using a Likert scale and documentation methods. The variables examined include subjective norms, the role of village officials, education level, tax sanctions, and religiosity as independent variables, with taxpayer compliance as the dependent variable. Data analysis utilized multiple linear regression with classical assumption tests, F-tests, t-tests, and the coefficient of determination. The results indicate that subjective norms, the role of village officials, and education level do not significantly affect tax compliance. Conversely, tax sanctions and religiosity have a significant influence. The limitations of this study include a restricted research area and the absence of moderating or mediating variables. Future research is recommended to expand the research scope and incorporate additional variables such as tax socialization, income levels, and service quality for a more comprehensive analysis.